Authorship as a linguistic sign in gender(s) inequality of journalistic temporalities - Ávalos Troncoso, María José (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
The objective of this article was to identify and discuss linguistic use with gender(s) perspective(s) in journalistic practices compared to the analog-digital transition through time according to style by authorship. Hence, it is necessary to ask whether the formation of social imaginaries together with the construction of binarism erect a differentiated writing system between authors-readers, which allows the continuity of a heterocispatriarchal story and re-presentation despite technological transformations, changes of platforms and new ways of communicating (us). In this case, a longitudinal section database was used for both the newspaper La Nación in its printed version and its digital version between 2008 and 2010. In aggregate terms, more than 200 articles were analyzed in a correlational way, where the analog and digital versions of the newspaper regarding attributed authorship.